Implementation of Problem Based Learning to Enhance Critical Thinking Skills in Social Studies at Madrasah Ibtidaiyah Islamiyah Kedungwaru Ngawi - Abdul Aziz Binsa; Wiwit PurnamaPutri (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The implementation of the Problem-Based Learning (PBL) model has proven to be effective in enhancing students’ critical thinking skills by encouraging active engagement in solving real-world problems. This study aims to improve students’ critical thinking skills through the application of the Problem-Based Learning (PBL) model in Social Studies instruction at MI Islamiyah Kedungwaru Ngawi. The method employed is Classroom Action Research (CAR). The research subject comprised 25 first-grade students observed during the learning process. Data collection methods included quantitative data obtained through written tests at the beginning (pre-test) and end (post-test) of the research, and qualitative data derived from interviews and observations. This study was conducted over two cycles, each consisting of two meetings. The results indicate that the implementation of PBL significantly improved students’ critical thinking skills, as evidenced by an increase in the average critical thinking indicator scores from 59.6 in the pre-cycle, to 70.7 in Cycle I, and 81.0 in Cycle II. Moreover, students’ responses to PBL were positive, with increased engagement and motivation. Thus, the PBL model is proven effective in improving critical thinking skills in Social Studies learning, while also fostering a positive classroom environment. This study suggests the broader implementation of PBL model in school curricula.